Determination of Optimum Conditions for Biodiesel Synthesis from Bulk Palm Oil Using Red Mud-CaO Catalyst - Nurdianty, Sri; Usman, Thamrin; Rahmalia, Winda (agriTECH, 2025)
The synthesis of biodiesel from bulk palm oil using methanol and a heterogeneous catalyst, red mud-CaO, has been carried out. This research aimed to investigate the effect of the ratio of red mud-CaO, percent catalyst, and reaction time on the conversion of methyl ester. Red mud and CaO catalysts were obtained from calcining red mud and clay bath CaCO3 (calcium carbonate) waste at 200°C and 900 o C for 5 and 4 hours, respectively. Biodiesel synthesis was carried out by adding bulk palm oil:methanol (1:10 v/v) and red mud-CaO heated for 1, 2, and 3 hours at 65 o C. In addition, the reaction was followed using thin-layer chromatography (TLC) and Gas Chromatography-Mass Spectrophotometry (GC-MS). Optimum reaction conditions were obtained at the ratio of red mud-CaO (1:1 w/w), catalyst 5%, and time of 2 hours indicated by the total formation of methyl ester on TLC plate. Meanwhile, red mudCaO (1:1 w/w) catalyst was characterized by x-ray diffraction (XRD) and x-ray fluorescence (XRF) to determine the crystal structure and element composition. The analysis was carried out using Fourier transform infra-red (FTIR) to determine the functional groups of catalyst. XRD characterization results showed that there were 4 highest peaks, namely 29.29° (CaCO3 ), 33.99° and 17.93° (Ca(OH)2 ), and 11.59° (aluminum silicate mineral). The 4 highest elemental contents were Ca, Fe, Al, and Si. FTIR characterization showed the peak wavenumbers 3641.60 cm -1 (Ca(OH)2 ),1423.47 cm -1 (O-C-O bond of carbonate), 981.77 cm -1 and 986.69 cm -1 (Si-O), 875.68 cm -1 and 713.66 cm -1 (Ca-O), 366.48 cm -1 (Al-O), and 426.27 cm -1 (Fe-O). According to GC-MS analysis, the most formed methyl ester compositions were methyl oleate (47.35%) and methyl palmitate (40.13%).